Acknowledging Lifelong Learning Principles Within Work-based Studies: A Continuing Legacy for the Degree Apprenticeship. (1st March 2019) - Nottingham, Paula
There has recently been a renewal of interest in work-based learning pedagogy within higher education due to policy changes in the United Kingdom that have introduced degree level apprenticeships as a way to bridge the gap between learning in the workplace and professional education. While many academic practitioners are aware of the history of lifelong learning and policies associated with widening participation within work-based studies, others might be less aware of the practical implications of this legacy in terms of facilitating learning. To inform practice, exploratory interviews with graduates of a part-time work-based degree programme at a single institution in the south-east of England provide insights into why graduates value a more holistic process of learning as a foundation for academic study. Findings indicated that the broader practice knowledge in the work-based curriculum allows graduates to develop a lasting sense of ownership of their studies. Conclusions suggest that academic practitioners now planning work-based studies and degree apprenticeships could consider a wider framework of practice that incorporates fundamental principles from lifelong and work-based learning as well as disciplinary vocational content to inform curriculum. It is argued that aligning current and future work-based studies within higher education with these concepts could provide academic practitioners with a broader and more resilient pedagogic framework.